The Concept of Religious Moderation in Thematic Hadith Education as the Foundation of Students’ Faith and Character - Dewi atma junira; Nur Hidayat; Mohd Syaubari bin Othman (Genderang Asa: Journal of Primary Education, 2026)
This study aims to analyze how thematic hadith learning can instill religious moderation as the basis for shaping students' faith and character. Religious moderation is understood as a balanced, non-extreme religious attitude that is able to respect differences. In Islamic education, moderation not only serves to build harmonious social attitudes, but also strengthens true faith and noble character. This study uses the library research method by collecting and analyzing literature related to hadith, Islamic education, and religious moderation. The results of the study show that the values of moderation, such as tawassuṭ (middle way), tasāmuḥ (tolerance), tawāzun (balance), and i‘tidāl (justice), can be effectively applied through thematic hadith learning. This model not only adds to theoretical understanding but also encourages students to practice Islamic teachings in a balanced manner that is relevant to their daily lives. Thus, thematic hadith learning plays an important role in shaping students who have strong faith, moderate character, and are able to live harmoniously amid diversity. This study suggests further empirical research to observe the application of this model in schools or madrasas directly